Post-Disaster Investigation of the Malin Slope Failure Deccan Plateau, India - Mishra, Mallikarjun; Dugesar, Vikas; Raju, K.N.Prudhvi; Sarkar, Shraban; Vishwakarma, Mukesh (National Geographical Journal of India, 2022)
In the morning of 30th July 2014 at 07:30:00 (IST), a major part of the village Malin, located in the Western Ghats in Maharashtra was washed out and buried under a mass of mud, rock and plant debris. More than 150 peoples perished in the disaster. Primarily it was identified that extreme rainfall consecutively during 25 July to 30 July 2014 triggered the phenomenon. The present study makes an attempt to work out the events leading to devastating debris flow through mapping from high resolution remote sensing data of hillslope topography and land use of pre- and post-disaster dates. Digital elevation model generated from topographical map and high resolution remote sensing data from Google Earth image are used for the study. The steeply sloping plateau margin above the village as well as the gently sloping plateau top, were occupied by narrow strips of terraced agricultural fields with 1m to 2m high earthen retention walls/bunds. The question is what is the actual trigger that initiated the mass flow especially over the strip above Malin village? With incessant rain the fields over the plateau and the sloping strip turned into virtual ponds and water overflowed. The event appears to have been triggered because of bursting of retention walls/bunds of agricultural fields over the plateau surface leading to sudden surge of flow over the plateau margin. This flow uprooted a few trees at the plateau top edge which acted as surcharge in causing the mass to flow and the consequent disaster.